2021
DOI: 10.3389/fcimb.2021.625430
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analyses of Acinetobacter baumannii Clinical Isolates to Identify Drug Resistant Mechanism

Abstract: Acinetobacter baumannii is one of the main causes of nosocomial infections. Increasing numbers of multidrug-resistant Acinetobacter baumannii cases have been reported in recent years, but its antibiotic resistance mechanism remains unclear. We studied 9 multidrug-resistant (MDR) and 10 drug-susceptible Acinetobacter baumannii clinical isolates using Label free, TMT labeling approach and glycoproteomics analysis to identify proteins related to drug resistance. Our results showed that 164 proteins exhibited diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 113 publications
0
11
0
Order By: Relevance
“…Therefore, many recent studies report the proteomic pro les or proteomes of drug-resistant clinical isolates as well as bacteria with drug resistance which was induced in the laboratory. [13][14][15][16][17] Typically, the whole proteome is measured and to show differential expression of numerous proteins in various drug-resistant bacteria, including those related to metabolism, reactive oxygen species management, drug targets, DNA/RNA modi cation, etc. In the case of the proteomes of antibiotic-resistant Ab strains, researchers observed that β-lactamase expression was generally upregulated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many recent studies report the proteomic pro les or proteomes of drug-resistant clinical isolates as well as bacteria with drug resistance which was induced in the laboratory. [13][14][15][16][17] Typically, the whole proteome is measured and to show differential expression of numerous proteins in various drug-resistant bacteria, including those related to metabolism, reactive oxygen species management, drug targets, DNA/RNA modi cation, etc. In the case of the proteomes of antibiotic-resistant Ab strains, researchers observed that β-lactamase expression was generally upregulated.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of these are found in class A and D serine β-lactamases and class B metallo-β-lactamases, with the class D OXA-type serine β-lactamase being regularly detected in CRAb 17 19 . Previous studies have also reported that a variety of such OXA-type β-lactamases can be found in CRAb 19 ; however, there has been limited work done on attempting to selectively characterize the entire set of β-lactamases in a single strain and compare these with resistant mutants 20 23 .…”
Section: Introductionmentioning
confidence: 99%
“…The Gram-negative aerobic, non-motile, pleomorphic bacillus Acinetobacter baumannii [ 1 ] is a multidrug-resistant opportunistic pathogen, currently identified as one of the major causes of nosocomial infections in the healthcare system worldwide [ 2 ]. Moubareck et al defined A. baumannii as the main causative agent of pneumonia, sepsis, meningitis and urinary tract and wound infections [ 3 ], with it being correlated to a nosocomial mortality rate of up to 35% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%